Of Oestrogens and Sperm: A Review of the Roles of Oestrogens and Oestrogen Receptors in Male Reproduction - Dostalova, Pavla (Int J Mol Sci, 2017)
The crucial role that oestrogens play in male reproduction has been generally accepted; however, the exact mechanism of their action is not entirely clear and there is still much more to be clarified. The oestrogen response is mediated through oestrogen receptors, as well as classical oestrogen receptors’ variants, and their specific co-expression plays a critical role. The importance of oestrogen signalling in male fertility is indicated by the adverse effects of selected oestrogen-like compounds, and their interaction with oestrogen receptors was proven to cause pathologies. The aims of this review are to summarise the current knowledge on oestrogen signalling during spermatogenesis and sperm maturation and discuss the available information on oestrogen receptors and their splice variants. An overview is given of species-specific differences including in humans, along with a detailed summary of the methodology outcome, including all the genetically manipulated models available to date. This review provides coherent information on the recently discovered mechanisms of oestrogens’ and oestrogen receptors’ effects and action in both testicular somatic and germ cells, as well as in mature sperm, available for mammals, including humans.